Prospective superficial EPR in-vivo dosimetry study during hypofractionated radiotherapy of breast cancer patients treated with helical tomotherapy - Höfel, Sebastian; Gandalini, Matteo; Fix, Michael K.; Drescher, Malte; Zwicker, Felix (Radiation oncology, 2021)
In-vivo dosimetry (IVD) is a patient specific measure of quality control and safety during radiotherapy. With regard to current reporting thresholds for significant occurrences in radiotherapy defined by German regulatory authorities, the present study examines the clinical feasibility of superficial electron paramagnetic resonance (EPR) IVD of cumulative total doses applied to breast cancer patients treated with helical intensity-modulated radiotherapy (tomotherapy).